AKUNTABILITAS DAN TRANSPARANSI PEMERINTAH DESA TERHADAP PENGELOLAAN DANA DESA PADA DESA KOTO TELUK KECAMATAN HAMPARAN RAWANG KOTA SUNGAI PENUH: AKUNTABILITAS DAN TRANSPARANSI PEMERINTAH DESA TERHADAP PENGELOLAAN DANA DESA PADA DESA KOTO TELUK KECAMATAN HAMPARAN RAWANG KOTA SUNGAI PENUH - syah, ikram; herawaty, netty; Yustien, Reni (Jambi Accounting Review (JAR), 2024)
This research aims to determine the influence of village government accountability and transparency on the management of village funds in Koto Teluk Village, Hamparan Rawang District, Sungai Penuh City. The research method used is a quantitative descriptive research method. The data source used is primary data with data collection techniques using questionnaires. The sampling technique used purposive sampling, with sample criteria being the parties involved in preparing and reporting village funds so that a sample of 35 samples was obtained. The data analysis method uses multiple linear regression. The results of this research show that: Accountability has a positive effect on village fund management. Transparency has a positive effect on village fund management. The overall research results show that accountability and transparency have a positive effect on village fund management.